Research on Strategies to Enhance Students’ Physical Fitness from the Perspective of Sports Education Management - Jian, Fan (International Journal of Social Sciences and Public Administration, 2024)
In recent years, the physical health level of students has been declining annually, becoming a hot topic of widespread concern in society. By strengthening sports education management, optimizing sports curricula, enhancing the quality of teaching staff, and innovating health assessment systems, we can effectively improve students’ physical fitness and health conditions. This article analyzes the impact of sports education management on enhancing students’ physical fitness and health from the perspective of current student health status, proposing a series of enhancement strategies including building scientific sports curricula, improving the quality of sports teachers, improving school sports facilities, and innovating physical health assessment mechanisms. Research has found that systematic sports education management plays a significant role in promoting students’ physical health and can provide long-term protection for students’ healthy growth.